Integrating Solution-Focused Therapy (SFT) in Dealing with Psychological Distress among Malaysian Clients - Nurul Naimah Rose (Asian Social Work Journal, 2022)
Solution focused therapy is one of the growing therapies used among psychologists and counselors for helping clients with psychological distress conditions. Despite the increasing number of successful research on the treatment of solution focused therapy, there is no specific approach to apply the therapy among Malaysian clients. Literature shows that Malaysian clients shares similar orientation such as collectivism, past-time orientation and psycho-spiritual. They needed slightly different therapy approach than the westerner. Thus, this conceptual paper suggested a new counselling model that integrates the counselling orientations among Malaysian clients and the main techniques of the solution focused therapy. The model displays the relationship of relevance concepts which can be serves as guideline for counselors and as a fundamental for research and practices of solution focused therapy counselling in Malaysia.